Foucault e a arte do cuidado de si: uma nova possibilidade de Discussão para a formação continuada de professores de língua inglesa - Santos, Ivonete Bueno dos (2012)
This thesis proposes a new thinking on the English teacher and their continuing education, leaving the picture emerging of a new professional, who is producing and being produced. From this perspective, I present an analysis of self writing of thirteen student-teachers, teachers on how they position themselves to be discursively constituted as subjects in the context of continuing education. As part of Applied Linguistics, the theory and method that supports the analysis of data are articulate key elements of Foucault notions, namely:The care of the self, seeking their connection with one another and care of and the self writing. In the theoretical notions of these elements are implied notions of others, such as speech, ethics, technology of the self, subject and truth. (Foucault, 1984, 1995, 2004c, 2006), and questioning the ethics of the subject. I propose to examine selected excerpts from the self writings of student teachers with a specialization in Teaching and Learning the English Language, seeking linguistic processes in the material production of subjectivities.In order to analyze the process of subjectivation, I examine the discursive statements of selected cuts, aiming to learn more specifically, the points of identification and fragments of the uniqueness of the teachers, showing how they care for themselves and reflect upon them in building their subjectivity from the technologies of the self, to occupy the position of English Language teachers. The results show that, in the exercise of self writing, the subject falls, and a practice of asceticism, discursively construct her/his subjectivity